Innovative Opportunities for Small Businesses in Tourism and the Application of Ethical Moral Principles - Pešić, Zoran; Cvetković , Zoran; Marković, Dragan (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2020)
The authors are starting from the thesis that the innovative possibilities of a small business in tourism are numerous, beginning from new content and processes to improvement of existing ones. At the same time, there are various obstacles whose overcoming requires creativity and inventiveness, as well as personal commitment. Obstacles are in limited financial, technical, and personal reasons, since small businesses are usually the property of one person or a smaller number of connected and close people. It was concluded that the innovation of small businesses can most be developed in tourism of special interests, where big businesses do not have big interest because of a smaller number of users, and that respect and personalization of ethical-moral principles additionally contribute to the development of small businesses.